The effect of mergers on variety in grocery retailing - Elena Argentesi; Paolo Buccirossi; Roberto Cervone; Tomaso Duso; Alessia Marrazzo (International Journal of Industrial Organization, 2021)
We study a merger between two Dutch supermarket chains to assess its effect on the depth as well as composition of assortment. We adopt a difference-in-differences strategy that exploits local variation in pre-merger competitive conditions and thus in the merger outcomes. To define our control group, we account for selection on observables through a matching procedure. We observe that, after the merger, the assortment of the merging parties converges in markets where they are not directly competing one with the other. Instead, the merging parties reposition their assortment to avoid cannibalization in the areas where they directly competed before the merger. While the target's stores reduce the depth of their assortment when in direct competition with the acquirer's, the latter increase their assortment. This suggests that variety is a strategic variable in retail chains' response to changes in local competition.
Keywords: L1; L41; L66; L81; D22; K21; C23; 330; Variety; Assortment; Mergers; Ex-post evaluation; Retail sector; Supermarkets; Grocery